Estimativas das trocas líquidas de carbono em duas áreas de cultivo de arroz irrigado na região central do RS - Carneiro, Janaína Viário (2012)
The turbulent fluxes of carbon dioxide (CO2 ) were investigated in two sites of irrigated rice in southern Brazil, using the eddy covariance technique over 385 days of analysis at the site of Paraiso do Sul and 683 days in site Cachoeira do Sul also used the model of filling the gaps in order to estimate the net ecosystem exchange CO2 -C (NEE). Throughout the growing season, rice fields, both for the site of Paraiso do Sul to the site of Cachoeira do Sul, acted as carbon sinks (C). During fallow periods, these fields were the source of C. The NEE accumulated at the site of Cachoeira do Sul was similar in both cycles and practically equal to the estimated site of Paraiso do Sul. The GPP accumulated during the crop cycle 2010-2011, the rice field of Cachoeira do Sul, was less than 12% of the 2011-2012 cycle and higher than 15% of the site of Paraiso do Sul. The Re accumulated was similar at the site of Paraíso do Sul in the 2010-2011 cycle Cachoeira do Sul, but less than the 2011- 2012 cycle. The values of NEE, GPP and R e for the site of Paraíso do Sul were - 270.53 gCm2 , -821.19gCm2 and 527.59gCm2 , respectively. To the site of Cachoeira do Sul, were -282,53 gCm2 , -933,40gCm2 and 597,05gCm2 for NEE, GPP and Re , respectively, in the 2010-2011 cycle. For the 2011-2012 cycle in the rice field of Cachoeira do Sul, the values of NEE, GPP and Re were -279,69gCm2 , - 1062,64gCm2 and 716,58gCm2 , respectively. The total C accumulated over the period analyzed for the site of Paraíso do Sul was -45,90gCm2 , considering this area of rice cultivation, as a sink for C. While the growing area of Cachoeira do Sul was considered a source of C (19,94 gCm2 ). Showing by this that long periods of fallow contribute significantly to the accumulated fluxes due to constant presence of vegetation. The contribution of this work will assist in the investigation of CO2 in these ecosystems.